Development of high-resolution melting PCR (HRM-PCR) assay to identify native fungal species associated with the wheat endosphere - Cłapa, Tomasz (J Appl Genet, 2020)
Understanding the complexity and biodiversity of fungal communities associated with the wheat endosphere can facilitate the identification of novel strains that might be beneficial to the host plant. However, the differentiation and taxonomic classification of the endosphere-associated fungi with respect to various cultivars and plant organs are challenging, time-consuming, and expensive, even with the use of molecular techniques. In the present work, we describe a fast, simple, and low-cost method based on high-resolution melting PCR (HRM-PCR) for the identification and differentiation of wheat endogenous fungal isolates. Using this approach, we differentiated 28 fungal isolates, which belonged to five different genera, namely Alternaria, Penicillium, Epicoccum, Fusarium, and Trichoderma. Furthermore, the results of the study revealed that this method can allow large-scale screening of cultured samples.